2018
DOI: 10.1021/acscatal.8b01936
|View full text |Cite
|
Sign up to set email alerts
|

Supported Embryonic Zeolites and their Use to Process Bulky Molecules

Abstract: X-ray amorphous zeolite precursors, embryonic zeolites, are prepared using tetrapropylammonium (TPA+) hydroxide as a structure directing agent. Their physicochemical properties are compared to those of a highly crystalline zeolite ZSM-5. Embryonic zeolites contain fewer acid sites, but their micropore volume and S BET area are higher than crystalline MFI-type material synthesized with TPA+. They can be introduced in the mesopores of a shaped silica-doped alumina matrix by two procedures: (i) impregnation of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…Another approach to increase the accessibility of active sites is to use amorphous zeolite seeds (3–4 nm in size) as so‐called embryonic zeolites. [ 91 ] Embryonic ZSM‐5 zeolites possess larger pore sizes than the corresponding crystalline zeolite as evidenced by a lower 129 Xe chemical shift. The xenon signal in the embryonic zeolites is narrower, pointing toward a more open structure and faster exchange.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Another approach to increase the accessibility of active sites is to use amorphous zeolite seeds (3–4 nm in size) as so‐called embryonic zeolites. [ 91 ] Embryonic ZSM‐5 zeolites possess larger pore sizes than the corresponding crystalline zeolite as evidenced by a lower 129 Xe chemical shift. The xenon signal in the embryonic zeolites is narrower, pointing toward a more open structure and faster exchange.…”
Section: Recent Applicationsmentioning
confidence: 99%
“…Our group also synthesized ZSM-5 materials containing amorphous silica matrix using aluminum nitrate as Al source for the first time without using any organic template [35]. Many research groups have reported on the synthesis and characterization of ZSM-5 materials embedded in amorphous silica, but these materials were not explored for catalytic application in the MTO process [36]. In this research, H-ZSM-5 materials with different Si/Al ratios (40, 45, and 50) embedded in amorphous silica were synthesized; the acid-site density of the H-ZSM-5 materials decreased by intercepting the crystallization process and making use of a unified crystallization time of 16 h. The physico-chemical properties were studied by different methods and the materials were used as catalysts in the MTO process.…”
Section: Structure Morphology and Porosity Of Synthesized Materialsmentioning
confidence: 99%
“…Our group also synthesized ZSM-5 materials containing amorphous silica matrix using aluminum nitrate as Al source for the first time without using any organic template [35]. Many research groups have reported on the synthesis and characterization of ZSM-5 materials embedded in amorphous silica, but these materials were not explored for catalytic application in the MTO process [36].…”
Section: Introductionmentioning
confidence: 99%
“…59 Although the secondary amorphous phases demonstrate some spectroscopic and size-exclusive characteristics of zeolites, the lack of long-range periodicity of a crystalline zeolite lattice makes it amorphous and unsuitable for X-ray diffraction (XRD). [22][23][24][25] Therefore, these zeolite precursors are also regarded as X-ray amorphous zeolites or embryonic zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…26 Recently, Haw et al prepared X-ray amorphous ZSM-5 precursors with tetrapropylammonium hydroxide (TPAOH) as the structure directing agent, which presented superior catalytic performances in the dealkylation of 1,3,5-triisopropylbenzene, which cannot penetrate through the micropores of zeolites. 24 The above demonstrated high catalytic activities of the amorphous titanosilicate zeolites were ascribed to the more open structure of X-ray amorphous zeolites, which dramatically increased the accessibility towards the catalytic active sites and enhanced the mass transport efficiency.…”
Section: Introductionmentioning
confidence: 99%